Efficacy and safety of current therapies for genitourinary syndrome of menopause: A Bayesian network analysis of 29 randomized trials and 8311 patients. (February 2021) - Li, Bohan; Duan, Hua; Chang, Yanan; Wang, Sha
Graphical abstract: Screening flow and network analysis diagram. A) We searched through PubMed, Embase, Scopus, Cochrane Library, Web of Science and ScienceDirect electronic databases, clinicaltrials.gov and OVID for relevant data on Genitourinary syndrome of menopause. Finally, 29 randomized trials and 8311 patients were included in the Bayesian Network analysis. B) The diagram demonstrates the relationship between the current treatments and their effectiveness against multiple GSM symptoms based on the network analysis. Circular nodes indicate treatment regimens. The size of each circle corresponds with the number of participants, whereas the colors represent the types of treatment options (pink for laser, green for DHEA, red for vaginal estrogen, orange for Ospemifene, blue for moisturizer/lubrication and yellow for placebo). The width of each line indicates the number of studies that is marked above each edge. Abstract: Genitourinary syndrome of menopause (GSM) seriously affects the quality of life of women in this stage and patients with breast cancer, but optimal treatment options as well as risks associated with the complication remain controversial. We aimed at exploring the safest and most effective treatment for genitourinary syndrome of menopause. The study was performed following a pre-established protocol registered on PROSPERO (CRD42020180807). We searched through PubMed, Embase, Scopus, Cochrane Library, Web of Science and ScienceDirect electronic databases, clinicaltrials.gov and OVID for relevant data on Genitourinary syndrome of menopause provided by March 2020. Randomised controlled trials (RCTs) on women presenting with some or all the signs and symptoms for genitourinary syndrome of menopause were extracted and analyzed based on the Bayesian theory. The key variables were additionally evaluated using the network sub-analyses, standard pairwise comparisons, regression analysis and subgroup and sensitivity analyses. The pooled estimates were quantified as odd ratios or mean differences where appropriate, at 95 % confidence intervals. In the end, 29 randomized controlled trials (RCTs) evaluating 5 different treatment regimens for genitourinary syndrome of menopause, involving 8311 patients, were included in the study. Laser therapy had excellent effect on vaginal dryness, dysparunia, urinary incontinence, proportion of parabasal cells, pH and VHI. Vaginal estrogen also had significant effects on these aspects, although its effect was inferior to that of laser therapy. Ospemifene therapy was however superior to laser and vaginal estrogen therapies in ameliorating sexual function, however, it presents a high risk of developing adverse events and endometrial hyperplasia. Moisturizer/lubricant was effective on dysparunia, proportion of parabasal cells and vaginal pH. In regression analysis, age was an essential factor affecting vaginal dryness and pH treatment effect. Compared with other currently available interventional treatments for genitourinary syndrome of menopause, laser therapy, followed by vaginal estrogen, confers superior clinical outcomes for most aspects associated with the disease. In addition, they pose relatively low risks of developing adverse events. Ospemifene and DHEA therapies on their part significantly improve sexual function of women with GSM. A strong relationship between treatment effect and age provides insights for future studies on clinical treatment.